The Effect of Bone Morphogenetic Protein-2 on Chondrocyte-like Cells Derived from Degenerated Human and Canine Intervertebral Discs. Issue 1 (April 2016) - Bach, Frances; Bedate, Alberto Miranda; van Heel, Ferdi; Müller, Margot; Creemers, Laura; Ito, Keita; Benz, Karin; Meij, Björn; Tryfonidou, Marianna
Introduction: Both humans and dogs experience low back pain, which is related to intervertebral disc (IVD) degeneration. Biologic repair of the degenerated IVD is mainly based on growth factors that exert anabolic matrix effects, and mesenchymal stromal cells (MSCs) to replenish the cell population of the degenerated IVD. Thus far, the anabolic effects of different growth factors have not been compared. The aim of this study was to study the effect of the frequently used growth factors transforming growth factor β 1 (TGF-β1 ) and bone morphogenetic protein-2 (BMP-2) on canine and human chondrocyte-like cells (CLCs) from degenerated IVDs alone and in combination with MSCs. Material and Methods: CLCs from degenerated human, canine chondrodystrophic (CD) and non-chondrodystrophic (NCD) IVDs (Thompson score III) were cultured in micro-aggregates in base culture medium (negative control), or supplemented with TGF-β1 (10 ng/mL) or BMP-2 (100 or 250 ng/mL) for 28 days. The additive effect of MSCs was studied in CD CLCs. Canine male CD CLCs were cultured in an albumin-based hydrogel (3*10 6 cells/mL) with or without the addition of female bone marrow-derived MSCs (BMSCs) (CLC:BMSC 1:1) in control or 250 ng/mL BMP-2-supplemented culture medium for 28 days. Read out parameters were extracellular matrix (ECM) production (RT-qPCR, glycosaminoglycan (GAG) production, Safranin O/Fast Green staining, immunohistochemistry), cell proliferation (DNA content, RT-qPCR) and apoptosis (RT-qPCR). Results: TGF-β1 treatment increased GAG deposition in human and canine CLC micro-aggregates, but also induced collagen type I deposition and a fibrotic rim. The latter was not observed in BMP-2-treated micro-aggregates. 250 ng/mL BMP-2 was more potent than 100 ng/mL BMP-2 in increasing GAG deposition and DNA content in canine and human micro-aggregates. Similarly, in the hydrogel culture system, BMP-2 induced GAG and collagen type II deposition and a higher DNA content compared with untreated controls. DNA and GAG content of BMSC+CLC hydrogels was higher than hydrogels with CLCs alone in the absence of BMP-2. In the BMP-2-treated hydrogels, DNA content of BMSC+CLC was higher than hydrogels with CLCs alone; GAG deposition or release was comparable between BMSC+CLC and CLC alone in the presence of BMP-2. Conclusion: In two different 3D culture systems, BMP-2 exerted comparable regenerative effects as TGF-β1 on human and canine CLCs in terms of GAG deposition and cell proliferation, but BMP-2 did not induce fibrotic (re)differentiation as observed with TGF-β1 treatment. Moreover, in the BMP-2-treated BMSC:CLC-containing hydrogels, where only half of the amount of CLCs were seeded compared with CLC alone, the DNA content was higher and an equal amount of GAGs was deposited, indicating that the BMSCs exerted an additional, regenerative effect in addition to BMP-2 treatment. PCR for SRY:GAPDH genes on DNA will indicate the ratio male(CLCs):female(BMSCs) present at the end of the study. This will indicate whether the BMSCs exerted trophic effects or chondrogenically differentiated. Acknowledgments: This work was supported by an AOSpine Research Network grant (SRN2011_11) and the Dutch Arthritis Foundation (LLP22).